2021
DOI: 10.3390/children8090759
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Executive Functions in the Prediction of Prosocial Behavior in High School Students. An InterDisciplinary Approach between Neuroscience and Education

Abstract: One of the most analyzed variables in educational research is prosocial behavior, given its relevance and its application in favor of a culture of peace, the construction of solid democratic societies and the development of social justice. For this reason, it is necessary to extend the knowledge of predictors of prosocial behavior so that they can be transferred to teaching practice. The research reported here was carried out using a quantitative methodology through a survey, based on data collection instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…This conclusion is not surprising due to the fact that there is not a consensus of the interaction of their factors along the literature [ 10 , 44 ], so a direct effect among cultural variables and prosocial behavior cannot be found. However, this effect seems to be clearer when prosocial behavior is mediated by emotional intelligence, at least in adolescents [ 18 , 46 ]. That is why it can be concluded that emotional intelligence and its concomitant variables are better predictors of prosocial behavior than cultural variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is not surprising due to the fact that there is not a consensus of the interaction of their factors along the literature [ 10 , 44 ], so a direct effect among cultural variables and prosocial behavior cannot be found. However, this effect seems to be clearer when prosocial behavior is mediated by emotional intelligence, at least in adolescents [ 18 , 46 ]. That is why it can be concluded that emotional intelligence and its concomitant variables are better predictors of prosocial behavior than cultural variables.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional intelligence, on the other hand, showed few, but more cohesive, results, as they were explained in the introduction. However, emotional intelligence is expected to explain prosocial behaviors much more robustly, as there is consistency across numerous articles about the important role of emotional intelligence as a predictor of prosocial behavior [ 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Se tomó evidencia sobre validez concurrente mediante la estimación de la correlación entre la Escala de Conducta Prosocial y el TMMS-24; esto, dado que el modelo de cascada de la inteligencia emocional predice mejor desempeño en tareas interpersonales a mayor comprensión y regulación emocional (Martin-Raugh et al, 2016) y existe evidencia empírica importante que ha demostrado la correlación entre inteligencia emocional y conducta prosocial (Espino-Díaz et al, 2021). Para la evidencia de fiabilidad, se calculó Omega de McDonald y Alpha de Cronbach.…”
Section: Análisis De Datosunclassified
“…The literature has highlighted the relevance of emotion recognition and regulation in influencing subjective and group well-being [5,6]. This is true until the complete development of psychic maturity, which happens only with the achievement of emotional intelligence [7,8]. In particular, developing emotion recognition in children is fundamental to improving relationships with others and, consequently, the so-called collaborative intelligence [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This model is based on psychosynthesis, a transpersonal psychoanalytic theory that focuses on personal growth and development through practical techniques such as mindfulness, guided meditation [39,40], and CS [41]. The transpersonal approach is considered "the second-generation of mindfulness-based interventions" because it takes account of the whole person [8], including the natural tendency to transcendence and human cooperation [42].…”
Section: Introductionmentioning
confidence: 99%